He who dreams - Florence, Melanie (Orca limelights., 2017)
"When John discovers dancing, he finds himself facing ridicule from his soccer teammates and hostility from the dancers at the cultural center. To dance at the Pow Wow, he must learn to balance his responsibilities, confront his fears and embrace both the Irish and the Cree sides of his heritage"--Back cover.